Persepsi Guru Qur’an Hadits terhadap Toleransi dalam Moderasi Beragama - Rusuli, Izzatur; Nazaruddin , Nazaruddin; Abdussyukur (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2023)
Currently religious moderation is the main program promoted by the Indonesian Ministry of Religion so that Indonesian Muslims act moderate in religion. This study aims to determine the perceptions of teachers of the Qur'an Hadith about religious moderation in the aspect of tolerance. This research is descriptive qualitative research using interviews and documentation as data collection techniques. The participants in this study were six Qur'an Hadith teachers and three headmasters. The results of the study show that the perceptions of the Qur'an Hadith teachers regarding tolerance in religious moderation are positive and they accept this concept where they agree that religious tolerance is mutual respect between religious communities in order to create harmonious social relations. They also considered that religious moderation must be developed continuously and taught to students.